Annual Meeting of Presidents and Administrators of The Superior Courts of Justice 2013 - s.a, s.a (2012)
Presents the declaration of Huaraz, on April 20, 2013, at the facilities of the Huaraz Cultural Center, meeting the members of the Executive Council of the Judiciary and the presidents of the 31 Superior Courts of Justice of Peru